Expanding assessment of fear of falling among older adults with an intellectual disability - MCCARRON, MARY; FORAN, SINEAD MARGARET (My University, 2013)
Fear of falling (FOF) has emerged as an important health concern in older adults, yet it has rarely been investigated in people with intellectual disabilities (ID). Valid and reliable measurement approaches are a particular challenge. Scales that have been developed to measure FOF have not been validated for use with older people with ID and are not routinely used with proxy respondents. Method. 63 people comprised purposeful samples of 3 groups, people with ID (? = 21), their nominated key workers (? = 21), and additional support workers (? = 21). Test-retest reliability and interrater reliability were assessed for using a dichotomous, single-item FOF screening measure. The degree of FOF and activity restriction due to FOF were also investigated. Results. Inter-rater reliability was found to be moderate to excellent with Kappa = 0.77 on ratings of the FOF item. Test-retest reliability for each group of reviewers for the FOF item were also found to be excellent (0.95). Conclusion. The global item is a suitable screening measure for FOF in older adults with ID and can assist in identification of individuals requiring further assessment. Proxies, if carefully selected, can provide consistent and reliable reports of the presence of FOF in people with ID.eri
PUBLISHED
Keywords: Geriatrics; Ageing